Rendimiento de excavadoras 390FL, 950E y costos unitarios de carguío en Minera Summa Gold Corporation SAC - Cerin De La Cruz, Anghelo Santos (2023)
The general objective of this study sought to determine how the performance of the CAT 390FL and Volvo 950E excavators are related to the unit costs of loading of the Minera Summa Gold Corporation SAC; through a non-experimental, descriptive design, of an application type and a quantitative approach, with a sample population where all the CAT 390 FL and Volvo 950E excavators that serve Summa Gold Corporation SAC participated; being the study variables analyzed through observation and documentation, since each of the machinery was used to evaluate its production, time, costs and cycles. Among the results, the performance between the CAT390FL excavators and the Volvo 950E was compared; in the smooth front performance CAT390FL obtained a performance of 1290.41 Tn/hr and Volvo 950E obtained a performance of 1347.25 Tn/hr, having cycles equal to 500 trips, in addition, the average was 1.34 minutes for the Volvo 950E excavator and the average it was 1.36 minutes for the CAT 390FL excavator. Concluding that there is a relationship between performance and unit loading costs, since unit costs of 0.139 US$/Tn were presented for the CAT390FL and 0.137 US$/Tn for the Volvo950E, with a significance of 0.001 and a direct relationship of 90.1. %; having a utilization of 85% for both cases.